2018
DOI: 10.1002/app.46367
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric hybrid films with photocatalytic activity under visible light

Abstract: The immobilization of photocatalysts on several kinds of substrates has been widely studied over the past few years, focusing mainly on improving its industrial application. In this work, novel hybrid films were prepared, employing TiO2 P25, commercial ZnO or BiOI, synthetized through hydrothermal method and immobilized on poly(vinylidene fluoride) by the non‐solvent‐induced phase inversion technique. Subsequently, the prepared composites were evaluated by photodegradation of methylene blue (MB) under ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…For example, TiO 2 and ZnO and BiOI encapsulated in poly(vinylidene fluoride) (PVDF) have demonstrated effective photocatalytic degradation of methylene blue both under visible and UV irradiation. 11 The optical properties of polymers extend the use of semiconductor nanoparticles beyond the tailoring of mixed matrix polymeric membranes for better solute rejection and solvent transport. The polymer in the mixed matrix membrane functions as a co-photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TiO 2 and ZnO and BiOI encapsulated in poly(vinylidene fluoride) (PVDF) have demonstrated effective photocatalytic degradation of methylene blue both under visible and UV irradiation. 11 The optical properties of polymers extend the use of semiconductor nanoparticles beyond the tailoring of mixed matrix polymeric membranes for better solute rejection and solvent transport. The polymer in the mixed matrix membrane functions as a co-photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Optical studies on photocatalyst‐embedded membranes have demonstrated that the photocatalyst also tailors the optical properties of the polymer‐which results in the mixed matrix membrane possessing optical properties that are unique to the membrane. For example, TiO 2 and ZnO and BiOI encapsulated in poly(vinylidene fluoride) (PVDF) have demonstrated effective photocatalytic degradation of methylene blue both under visible and UV irradiation 11 . The optical properties of polymers extend the use of semiconductor nanoparticles beyond the tailoring of mixed matrix polymeric membranes for better solute rejection and solvent transport.…”
Section: Introductionmentioning
confidence: 99%
“…Sem capacitação docente, o professor tende a utilizar seu contexto histórico de como aprendeu durante a vida acadêmica e seu próprio estilo de aprendizagem para ministrar suas aulas, o que pode influenciar negativamente no processo de aprendizagem do próprio aluno. (Zanrosso;Costa;Kinast, 2018, p. 2) Os resultados da pesquisa sugeriram que os docentes analisados não possuem, em sua maioria, qualificação nas áreas da Educação para atuação docente, apenas 5% possuem especialização em Educação e 30% estão qualificados através de cursos de extensão ou pesquisa em áreas relacionadas a Educação. Essa situação, de baixa qualificação em educação, pode demonstrar a tendência da qualificação dos docentes engenheiros nas outras instituições do país.…”
unclassified
“…Corroborado a isso está o fato de que os currículos dos cursos de engenharia não contribuem para a formação na área de educação; como se a docência não fosse uma opção para engenheiros (Zanrosso;Costa;Kinast, 2018, p. 8). Outro ponto abordado pelos autores diz respeito a resistência dos professores por programas de aperfeiçoamento, que segundo eles se deve a não valorização por parte da instituição sobre o desempenho do professor em sala de aula (Zanrosso;Costa;Kinast, 2018, p. 8).…”
unclassified